Implementasi Sistem Informasi dalam Manajemen Pendidikan Di SDIT Indra Bangsa - Zulfa, Gina Indonesia (INTIFA: Journal of Education and Language, 2024)
ABSTRACK This research describes the implementation of Information Systems in Education Management at SDIT Indra Bangsa. The Education Management Information System is progressing to meet the needs of madrasa/school institutions, with schools agreeing to computerized management of academic activities as a collaboration in improving the quality of madrasa/school services aimed at facilitating school services and the process of teaching and learning activities. This research uses a qualitative approach using observation, interviews and documentation as data collection techniques. The results of this research show that the implementation of the education management information system at SDIT Indra Bangsa is in the form of utilizing an application system consisting of educational and educational services. One of the innovations is by providing a Belajar.id account from the Ministry of Education and Culture to access various platforms. independent teaching platform, education report cards, BOS and BOP questions, teacher and staff fingerprint applications and web-based applications for accepting new students. There are several supporting and inhibiting factors in implementing SIMDIK at SDIT Indra Bangsa, namely the availability of information system facilities and the existence of obstacles in human resources as well as technical errors as well as teacher obstacles in studying the material in the application. ABSTRAK Penelitian ini mendeskripsikan implementasi Sistem Informasi dalam Manajemen Pendidikan di SDIT Indra Bangsa. Sistem Informasi Manajemen Pendidikan kemajuan untuk memenuhi kebutuhan lembaga madrasah/ sekolah, pada sekolah menyutujui pengelolaan kegiatan akademik yang terkomputerisasi sebagai kolaborasi dalam meningkatkan kualitas pelayanan madrasah/ sekolah bertujuan mempermudah dalam pelayanan sekolah dan proses kegiatan belajar mengajar. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. hasil penelitian ini menunjukkan bahwa implementasi sistem informasi manajemen pendidikan di SDIT Indra Bangsa dalam bentuk pemanfaatan sistem aplikasi yang terdiri dari pelayanan pendidik dan kependidikan salah satu inovasi yang dilakukan dengan memberikan akun belajar.id besutan kemendikbudristek dalam mengakses berbagai platform. platform merdeka mengajar, rapor pendidikan, tanya BOS dan BOP, aplikasi fingerprint guru dan staff dan aplikasi berbasis web dalam penerimaan peserta didik baru (PPDB). Ada beberapa faktor pendukung dan penghambat dalam implementasi SIMDIK di SDIT Indra Bangsa adalah tersedianya fasilitas sistem informasi dan adanya kendala dalam sumber daya manusia maupun kesalahan teknis serta kendalan guru dalam mempelajari materi pada aplikasi tersebut.